2023
DOI: 10.1002/adom.202202883
|View full text |Cite
|
Sign up to set email alerts
|

Zn (II)‐Doped Cesium Copper Halide Nanocrystals with High Quantum Yield and Colloidal Stability for High‐Resolution X‑Ray Imaging

Abstract: and adjustable bandgap, thereby exhibiting extraordinary X-ray detection performance. [1] To date, high-quality lead-based perovskite single crystals have demonstrated ultrahigh detection performance. However, they are limited by their current shortcomings, including the toxicity of lead, chemical instability, inherent brittleness of bulk crystals, and their hightemperature fabrication and complex processes. [2] Therefore, the development of low-cost, environmentally friendly, flexible X-ray detectors, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…However, there are still some problems to be solved in order to achieve practical commercial applications of copper-based metal halide scintillators. First, the intrinsic poor stability makes metal halide scintillators exposed to the air, making it difficult to achieve long-term applications. , Second, the surface defects can hugely decrease the RL efficiency of scintillator nanocrystals (NCs), which makes it difficult to achieve high-resolution X-ray imaging. , The third issue is that currently most scintillator devices are packaged with a simple mixture of powder scintillators and polymers, which makes it difficult to obtain high-quality and uniform scintillator films. Based on this, the development of in-situ crystalline scintillator films can effectively solve the instability and packaging problems of copper-based metal halide and can also achieve flexible X-ray imaging. In our former research, it found that the CsPbBr 3 NCs can in-situ grow in precured polymer polymethyl methacrylate (PMMA) with high viscosity like as a “polymer ceramics”, which achieved flexible and high-resolution X-ray imaging .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are still some problems to be solved in order to achieve practical commercial applications of copper-based metal halide scintillators. First, the intrinsic poor stability makes metal halide scintillators exposed to the air, making it difficult to achieve long-term applications. , Second, the surface defects can hugely decrease the RL efficiency of scintillator nanocrystals (NCs), which makes it difficult to achieve high-resolution X-ray imaging. , The third issue is that currently most scintillator devices are packaged with a simple mixture of powder scintillators and polymers, which makes it difficult to obtain high-quality and uniform scintillator films. Based on this, the development of in-situ crystalline scintillator films can effectively solve the instability and packaging problems of copper-based metal halide and can also achieve flexible X-ray imaging. In our former research, it found that the CsPbBr 3 NCs can in-situ grow in precured polymer polymethyl methacrylate (PMMA) with high viscosity like as a “polymer ceramics”, which achieved flexible and high-resolution X-ray imaging .…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Second, the surface defects can hugely decrease the RL efficiency of scintillator nanocrystals (NCs), which makes it difficult to achieve high-resolution X-ray imaging. 31,32 The third issue is that currently most scintillator devices are packaged with a simple mixture of powder scintillators and polymers, which makes it difficult to obtain high-quality and uniform scintillator films. 33−38 Based on this, the development of in-situ crystalline scintillator films can effectively solve the instability and packaging problems of copper-based metal halide and can also achieve flexible X-ray imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, developing nontoxic, luminescent nanocrystals that exhibit a greater stability while retaining their optoelectronic capabilities, unlike perovskite nanocrystals, is crucial. [ 17,18 ] Owing to their relatively low toxicity and earth‐abundant constituents, [ 19–21 ] Cs 3 Cu 2 X 5 ( X = I, Br, and Cl) nanocrystals have recently come under the spotlight as fascinating alternatives to lead halide perovskites. [ 20–22 ] In addition, these nanocrystals feature a unique self‐trapped exciton (STE) emission mechanism, [ 23,24 ] which results in a high quantum yield and emission stability.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, developing nontoxic, luminescent nanocrystals that exhibit a greater stability while retaining their optoelectronic capabilities, unlike perovskite nanocrystals, is crucial. [17,18] Owing to their relatively low toxicity and earth-abundant constituents, [19][20][21] Cs 3 Cu 2 X 5 (X = I, Br, and Cl) nanocrystals have recently come under the spotlight as fascinating alternatives to lead halide perovskites. [20][21][22] In addition, these nanocrystals feature a unique self-trapped exciton (STE) emission mechanism, [23,24] which results in a high quantum yield and emission stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation